Alcohol and Liver Clock Disruption Increase Small Droplet Macrosteatosis, Alter Lipid Metabolism and Clock Gene mRNA Rhythms, and Remodel the Triglyceride Lipidome in Mouse Liver - Valcin, Jennifer A.; Udoh, Uduak S.; Swain, Telisha M.; Andringa, Kelly K.; Patel, Chirag R.; Al Diffalha, Sameer; Baker, Paul R. S.; Gamble, Karen L.; Bailey, Shannon M. (Frontiers in Physiology, 2020)
Heavy alcohol drinking dysregulates lipid metabolism, promoting hepatic steatosis – the first stage of alcohol-related liver disease (ALD). The molecular circadian clock plays a major role in synchronizing daily rhythms in behavior and metabolism and clock disruption can cause pathology, including liver disease. Previous studies indicate that alcohol consumption alters liver clock function, but the impact alcohol or clock disruption, or both have on the temporal control of hepatic lipid metabolism and injury remains unclear. Here, we undertook studies to determine whether genetic disruption of the liver clock exacerbates alterations in lipid metabolism and worsens steatosis in alcohol-fed mice. To address this question, male liver-specific Bmal1 knockout (LKO) and flox/flox (Fl/Fl) control mice were fed a control or alcohol-containing diet for 5 weeks. Alcohol significantly dampened diurnal rhythms of mRNA levels in clock genes Bmal1 and Dbp, phase advanced Nr1d1/REV-ERBα, and induced arrhythmicity in Clock, Noct, and Nfil3/E4BP4, with further disruption in livers of LKO mice. Alcohol-fed LKO mice exhibited higher plasma triglyceride (TG) and different time-of-day patterns of hepatic TG and macrosteatosis, with elevated levels of small droplet macrosteatosis compared to alcohol-fed Fl/Fl mice. Diurnal rhythms in mRNA levels of lipid metabolism transcription factors (Srebf1, Nr1h2, and Ppara) were significantly altered by alcohol and clock disruption. Alcohol and/or clock disruption significantly altered diurnal rhythms in mRNA levels of fatty acid (FA) synthesis and oxidation (Acaca/b, Mlycd, Cpt1a, Fasn, Elovl5/6, and Fads1/2), TG turnover (Gpat1, Agpat1/2, Lpin1/2, Dgat2, and Pnpla2/3), and lipid droplet (Plin2/5, Lipe, Mgll, and Abdh5) genes, along with protein abundances of p-ACC, MCD, and FASN. Lipidomics analyses showed that alcohol, clock disruption, or both significantly altered FA saturation and remodeled the FA composition of the hepatic TG pool, with higher percentages of several long and very long chain FA in livers of alcohol-fed LKO mice. In conclusion, these results show that the liver clock is important for maintaining temporal control of hepatic lipid metabolism and that disrupting the liver clock exacerbates alcohol-related hepatic steatosis.